Email marketing in a digital world : the basics and beyond - Hanna, Richard C.; Swain, Scott D.; Smith, Jason (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Despite annual predictions of its demise, email marketing remains one of the most important tools for businesses and other organizations. The reason is simple. Other communication tools, including the collective proliferation of social and digital media channels, cannot duplicate or recreate the unique capabilities of email marketing. And do not let the name fool you--email marketing is not just for marketers. It is for anyone who can imagine the value of being able to reach specific people (and only those specific people) in a timely manner with messages and propositions while also having the ability to directly measure their responsiveness and reactions. This book is intended for those who wish to learn more about how email marketing works, whether as students, teachers, or practitioners. We begin with a recap of the history of email and email marketing and explain how it informs email today. We then cover the fundamentals of email marketing, including types of emails, the elements of an email, email metrics, best practices for email for improving performance, list development, and the benefits of segmenting an email list. Thereafter, we examine special topics to help managers address special needs in email strategy, including the personalities of email recipients, how to run a proper A/B test for optimizing email elements, integrating email with social media efforts, and aligning email with data sources and CRM opportunities.
Part 1. What everyone should know about email -- 1. Email still matters -- 2. You've got mail! A trip down memory lane -- 3. The anatomy of an email and email environments -- 4. The metrics of email marketing -- Part 2. Email marketing strategy -- 5. Consumer decision making and the role of email -- 6. Making a list that is worth its weight in gold -- 7. Optimizing emails and A/B testing -- Part 3. Beyond the basics of email -- 8. The personalities of email users -- 9. Social media and email: friend, ally, or frenemy? -- 10. Integrating email with big data -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on January 18, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Internet marketing; Electronic mail messages; Email marketing; email metrics; email history; CAN-SPAM; A/B testing; social media; email lists; segmentation; big data; Electronic books